Flexible flight response to challenging wind conditions in a commuting Antarctic seabird: do you catch the drift? - Tarroux, Arnaud; Weimerskirch, Henri; Wang, Sheng-Hung; Bromwich, David H.; Cherel, Yves; Kato, Akiko; Ropert-Coudert, Yan; Varpe, Øystein; Yoccoz, Nigel G.; Descamps, Sébastien (Animal behaviour, 2016)
Flight is intrinsically an energetically costly way of moving and birds have developed morphological, physiological and behavioural adaptations to minimize these costs. Central-place foraging seabirds commute regularly between nesting and foraging areas, providing us with opportunities to investigate their behavioural response to environmental conditions that may affect flight, such as wind. Here we tested hypotheses on how wind conditions influence flight behaviour in situations devoid of the confounding effect that, for instance, active foraging behaviour can have on movement patterns. We studied the Antarctic petrel, Thalassoica antarctica, a seabird breeding far inland in Antarctica and commuting through vast ice-covered areas characterized by steady and strong winds as well as a strict absence of foraging opportunities. We combined the three-dimensional location data from 79 GPS tracks with atmospheric wind data over three consecutive breeding seasons (2011–2013) in order to assess individual flight responses to wind conditions. Antarctic petrels encountered generally unfavourable winds, particularly during return flights. Despite their capacity to adjust their speed and heading in order to maintain constant track direction (compensation) in the strongest winds, they generally drifted as wind strengthened. Strong winds induced low-altitude flight. Birds tended to otherwise fly relatively high, but at altitudes with more favourable winds than what they would have encountered if flying higher. Our results show that commuting Antarctic petrels: (1) can tolerate a certain amount of drift according to wind conditions and (2) might be more limited by their ability to assess drift, rather than compensate for it, at least during returning flights. •We examine flying tactics of Antarctic petrels during commuting in harsh winds.•In favourable winds, high-altitude flight is preferred.•Strong unfavourable winds (head or cross winds) induce near-ground level flight.•Birds drift more in strong winds during outbound and return flights.•Our results suggest that birds may have difficulty assessing drift in strong winds.